Bubbling Up the Good Ideas: A Two-Mode Network Analysis of an Intra-Organizational Idea Challenge. Issue 3 (9th May 2016) - Stephens, Bryan; Chen, Wenhong; Butler, John Sibley
Abstract: Organizations have been experimenting with intraorganizational crowdsourcing (IOC), yet the mechanisms of IOC production remain an underresearched topic. Drawing on a 2-mode ERGM, we examine structural mechanisms and individual-level factors that shape the network structure of idea generation and selection yielded by an IOC idea challenge in a global IT corporation. Results show a Matthew effect leading to 1) highly centralized employee participation around a few "superactive" employees who engage with many ideas and 2) highly centralized idea popularity with a few ideas attracting most employee attention. We find support for shared affiliations among employee-idea clusters in the first half of the participation, which is, however, less likely in the second half. We also find support for geographic homophily.